Cyclical response of maize populations versus base population and standard genotypes across environments - Sajjad, Mohammad; Ullah Khan, Naqib; Gul, Samrin; Ullah Khan, Shahid; Bibi, Zarina; Ali, Sardar; Aslam Khan, Sher; Ali, Naushad; Tahir, Iqra; Habib, Amina; Hussain, Ijaz (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Recurrent selection is a cyclical breeding procedure in which selection is made generation after generation, with a reunion of selected plants to produce a new population for the next cycle of selection. Maize (Zea mays L.) base population ‘PSEV3’ was developed by using selfed progeny recurrent selection in spring and summer crop seasons during 2014 to 2016. During Summer 2017, two improved maize populations [PSEV3-(S1)-C1 and PSEV3-(S2)-C2], original genotype (PSEV3-C0) and three check varieties (two OPV - open-pollinated varieties - Azam and Jalal, and HV - hybrid variety - Kiramat) were assessed for silking and yield traits across four environments including two planting dates and two sites i.e., Cereal Crops Research Institute (CCRI), Pirsabak - Nowshera, and University of Agriculture (UAP), Peshawar, Pakistan. Genotypes and planting dates enunciated significant (p≤0.01) differences for majority of the traits. Maize improved populations (C1 and C2) enunciated comparable values with early flowering and least cob height compared to base population and check genotypes. On average, PSEV3-(S2)-C2 was foremost and exhibited maximum mean values for yield traits with enhanced grain yield with optimum planting at CCRI, followed by PSEV3-(S1)-C1. Base population - C0 and check genotypes were observed with delayed silking and least grain yield across the environments. Selfed progeny recurrent selection was established as an efficient breeding method in improving maize base populations.